Lumbar disc herniation in adolescence - DAĞÇINAR, ADNAN (KARGER, 2007)
Lumbar disc herniation very rarely occurs in adolescence. The aim of this study was to assess the radiological, clinical and surgical features and case outcomes for adolescents with lumbar disc herniation, and to compare with adult cases. The cases of 17 adolescents (7 girls and 10 boys, age range 13-17 years) who were surgically treated for lumbar disc herniation in our clinic between 1998 and 2003 were retrospectively reviewed. The mean follow-up time for these cases was 60 months. The collected histories revealed that 14 (82%) of the 17 cases involved trauma or intense sports activity. Low back pain was the most common complaint (15 cases, 88%). None of the 17 patients had major symptoms during follow-up, and most were engaged in intense sports or heavy work-related activities during this period. The main features of lumbar disc herniation in adolescents are different from those seen in adults. Careful assessment is vital to avoid misdiagnosis and prevent undesirable results from inappropriate surgery. When surgery is indicated and patients are carefully selected, the results of lumbar discectomy in adolescence can be satisfactory. Copyright (c) 2007 S. Karger AG, Basel
Keywords: low back pain; disc herniation; adolescents; INTERVERTEBRAL DISC; NERVE ROOTS; CHILDREN; EXCISION; DEGENERATION; PROTRUSION; ANOMALIES; SPINE